Overcoming Barriers for Breast Cancer Detection in Women with High Breast Density [Letter] - Wu X; Miao Y (Patient Preference and Adherence)
Xiaopeng Wu, Yanping Miao Department of Radiology, The Affiliated Hospital of Inner Mongolia Medical University, Hohhot, Inner Mongolia, People’s Republic of ChinaCorrespondence: Yanping Miao, Email miaoyanping810@126.com